Surgical treatment of humeral-shaft fractures: A register-based study in Finland between 1987 and 2009 - Huttunen, Tuomas T.; Kannus, Pekka; Lepola, Vesa; Pihlajamäki, Harri; Mattila, Ville M. (Injury, 2012)
Humeral-shaft fractures are not uncommon osteoporotic fractures. While most of the humeral-shaft fractures can be treated conservatively, some need surgical treatment. The purpose of this study was to assess the trends of the surgical treatment of humeral-shaft fractures. The study determined whether surgical treatment of humeral-shaft fractures has changed in Finland between 1987 and 2009. We assessed the number and incidence of surgically treated humeral-shaft fractures in each year and recorded the type of surgery used. The study covered the entire adult (>18 years) population in Finland over the 23-year period from 1 January 1987 to 31 December 2009. Data on surgically treated humeral-shaft fractures were obtained from the nationwide National Hospital Discharge Registry. During the 23-year study period, a total of 4469 surgical operations of the humeral shaft were performed in Finland. The male patients were markedly younger (49 years) than their female counterparts (63 years). The incidence of surgical treatment nearly doubled in men and over tripled in women. Between 1987 and 2009, there occurred a clear shift towards plating in the surgical treatment of humeral-shaft fractures. A marked increase in the surgical treatment of humeral-shaft fractures was seen in Finland in 1987–2009. Fracture plating increased during the first decade of the millennium. Since high-quality evidence for treatment of humeral-shaft fractures is absent, critical evaluation of the chosen treatment options is needed.